A study of 124 with cases carpal tunnel syndrome - AL-Shalchy, Ali K. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: carpal tunnel syndrome (CTS) a relatively common disease affecting ♀ more than ♂, usually at the age between 40 -60 , diagnosed by EMG & NCS, treated when moderate to severe by surgical decompression of the median nerve. Objective: To study the role of surgery in the management of CTS. Patients & method: 124 patients collected from the neuro-surgical departments of the specialized surgical hospital from August 2001 till March 2007, all patients studied thoroughly regarding age, sex, associated diseases, clinical features, EMG studies, surgery & out come & follow up for at least one year. Results & discussion: there was around 2:1 ♀:♂ , with age predomena between 40-60 years. All the patients had pain (aching) & most of them numbness, & tingling and only 1/3 had atrophy of muscle of the hand all diagnosed by EMG & NCS, treated surgically results were good compared with other studies regarding complications & final out come. Conclusion: surgery for CTS is safe & successful surgery under meticulus procedure & appropriate choice of patients.